High heritability of human facial traits reveals associations with CNTLN, BRCA1, and TMPRSS6 loci in Korean families - Donghyun Lee; Hyo-Jeong Ban; Kyung-Won Hong; Jong Young Lee; Seongwon Cha (Heliyon)
Facial features are determined by interactions between genetic and environmental factors. However, genes underlying facial similarities in individuals from the same family remain less explored. To identify genetic variants associated with heritable facial features, we investigated familial (parent–offspring) associations and estimated familial correlation and heritability using 39 facial measurements in 408 individuals from 117 Korean families. Facial trait heritability ranged from 0.124 to 0.669. Longitudinal facial growth-related traits were highly heritable, including distances from the nasion to right alare (h2 = 0.668898), pogonion to midendocanthion (h2 = 0.661557), subnasale to midendocanthion (h2 = 0.656882), and morphological facial height (h2 = 0. 654376). We identified the top three significant genome-wide associated variants in the eye, nose, and lip–jaw regions. CNTLN (rs10511632: beta = −0.02696, p = 1.146 × 10−9) and BRCA1 (rs397509305: beta = 0.02741, p = 7.17 × 10−9) loci were associated with distance from the nasion to the right alare. The TMPRSS6 (rs228913: beta = 0.05101, p = 3.68 × 10−9) locus was associated with the distance from the labiale superius to the pogonion and lower facial height. These associations were maintained in an independent unrelated population. In conclusion, we identified new gene variants associated with longitudinal facial morphology that may affect individual facial differences, which has important implications for clinical and forensic applications.